2013
DOI: 10.1111/ppe.12054
|View full text |Cite
|
Sign up to set email alerts
|

Social Modifications of the Multiple Birth Effect on IQ and Body Size: a Population‐Based Study of Young Adult Males

Abstract: Twins and triplets fall slightly behind singletons in cognitive and physical development, even in early adulthood, but twins and triplets show no major differences. These differences are largest in families in a low socio-economic position. Our results underscore the importance of the postnatal environment in the development of twins and triplets and suggest that their parents, especially those in a low socio-economic position, need special support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Furthermore, in all of these previous studies, the participants were born in the 1970s or later. Since there is clear evidence of the trend of lower IQs in twins compared to singletons in the earlier birth cohorts diminishing in the more recent birth cohorts (Silventoinen et al, 2013; Voracek & Haubner, 2008), it is possible that twins have also been behind singletons in school performance in the earlier birth cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in all of these previous studies, the participants were born in the 1970s or later. Since there is clear evidence of the trend of lower IQs in twins compared to singletons in the earlier birth cohorts diminishing in the more recent birth cohorts (Silventoinen et al, 2013; Voracek & Haubner, 2008), it is possible that twins have also been behind singletons in school performance in the earlier birth cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…The body mass index (BMI) of twins has been compared with that of singletons in several studies (Andrew et al, ; Estourgie‐van Burk et al, ; Poulsen et al, ; Silventoinen et al, ). Most of these studies indicated that twins are slimmer (Andrew et al, ; Estourgie‐van Burk et al, ; Silventoinen et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The body mass index (BMI) of twins has been compared with that of singletons in several studies (Andrew et al, ; Estourgie‐van Burk et al, ; Poulsen et al, ; Silventoinen et al, ). Most of these studies indicated that twins are slimmer (Andrew et al, ; Estourgie‐van Burk et al, ; Silventoinen et al, ). Such a difference in BMI between twins and singletons was found in studies of children (Estourgie‐van Burk et al, ) and adults (Andrew et al, ; Estourgie‐van Burk et al, ; Silventoinen et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study compared the IQ scores, body size and strength measures of Swedish twins and their non-twin siblings (Silventoinen et al, 2013). Participants were Swedish men born between 1951 and 1976.…”
Section: Multiple Birth Effects On Iq and Body Sizementioning
confidence: 99%